Synthese d’entretien le juge d’instruction du cabinet en charge des questions des enfants en conflits avec la loi; du Tribunal de Grande Instance de Ouaga 1 - Tapsoba, Tatiana Nadine (Criminal justice institutions and the social trajectories of adolescents/youth in Burkina Faso: endogenous/local forms and patterns of punishment, 2021)
This interview summary was with an examining magistrate in charge of issues relating to children in conflict with the law at the Tribunal de Grande Instance de Ouaga 1. This interview took place on April 15, 2021 and the exchanges focused on types of misconduct, mechanisms for dealing with misconduct committed, popular perception of forms of punishment for children, popular perception of prison as a form of punishment for children, and collaboration between traditional justice and modern justice.
Keywords: Administration of Justice; Teenagers; Youth; Punishment; Maintenance; Children; Conflict